Pengaruh Manajemen Kompensasi dan Kinerja Sumber Daya Manusia terhadap Kreativitas Guru pada SMK di Kecamatan Sawangan Kota Depok - Supriyati, Supriyati; Mukodim, Didin (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research is motivated by the important role of teacher performance in the education and learning process, especially in determining student learning outcomes. Teacher performance is a complex factor and involves understanding students' situations and the ability to create a conducive learning atmosphere. Apart from performance, the compensation received by teachers can also influence creativity in teaching. Therefore, this research was conducted to analyze the influence of human resource management compensation and teacher performance on teacher creativity in Depok City Vocational Schools. Teachers as research objects were chosen because they have a strategic role in improving the quality of education. The research method used is a quantitative approach with multiple regression analysis. This research involved the entire population of vocational school teachers in Depok City, with a total population of 150 teachers. However, the samples taken were 90 teachers from various backgrounds including gender, education level and age. Data was collected through questionnaires filled out by respondents. Variables in this research include compensation, teacher performance, and teacher creativity. Hypothesis testing was carried out to determine the relationship between variables and see the significant influence that emerged between teacher compensation and performance on teacher creativity. The research results show that compensation does not have a significant effect on teacher performance. However, teacher performance has a significant influence on teacher creativity. Simultaneously, teacher compensation and performance have a significant influence on teacher creativity. These findings emphasize the importance of improving teacher performance in an effort to encourage creativity, and provide an illustration that even though compensation does not show a significant direct effect, attention is still needed in its management to support optimal performance.